Podobe tujega v nemških potopisih 16. in 17. stoletja - Bole, Andreja (Vestnik za tuje jezike, 2013)
This paper points out the image of the Russian in the selected German travel accounts of the 16th and 17th century, through the eyes of the West European well-educated legate seen as a savage, boorish Barbarian. The image of the Russian illustrates the importance of the relationship between the one's own, civilized (here German) and the other, often barbaric (here Russian) cultural reality.
Keywords: Herberstein, Žiga, 1644-1716; Olearius, Adam, 1603-1671; nemška književnost; German-language literature; potopisi; podobe tujega; Rusija; 16.-17.st.